2020
DOI: 10.1186/s13071-020-04067-5
|View full text |Cite
|
Sign up to set email alerts
|

Pro-fibrinolytic potential of the third larval stage of Ascaris suum as a possible mechanism facilitating its migration through the host tissues

Abstract: Background: Ascaris roundworms are the parasitic nematodes responsible for causing human and porcine ascariasis. Whereas A. lumbricoides is the most common soil-transmitted helminth infecting humans in the world, A. suum causes important economic losses in the porcine industry. The latter has been proposed as a model for the study of A. lumbricoides since both species are closely related. The third larval stage of these parasites carries out an intriguing and complex hepatopulmonary route through the bloodstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
3
0
2
Order By: Relevance
“…All these results are in line with those obtained in the previous study, which showed the pro-fibrinolytic potential of AsL3 [ 18 ]. The present work reinforces the idea that AsL3 could modulate the haemostatic system of their host for their own benefit, not only through the dissolution of blood clots, but also preventing their formation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All these results are in line with those obtained in the previous study, which showed the pro-fibrinolytic potential of AsL3 [ 18 ]. The present work reinforces the idea that AsL3 could modulate the haemostatic system of their host for their own benefit, not only through the dissolution of blood clots, but also preventing their formation.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, we have recently demonstrated the capacity of the cuticle and excretory/secretory antigenic extracts of AsL3 (AsL3C and AsL3ES) to activate the host fibrinolytic system, which represents the mechanism of the haemostatic system responsible for dissolving blood clots [ 18 ]. In order to complement this study and contribute to the knowledge of the host-parasite relationships in porcine ascariosis, the present work was carried out with the aim of evaluating the ability of AsL3C and AsL3ES to inhibit the coagulation cascade of the host as a potential survival mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In a broader context, we have demonstrated how microCT offers an opportunity to reassess the life-cycles of other parasites, and characterize intra-tissue migration and establishment with additional clarity. For example, Ascaris is another soil transmitted helminth which migrates through the lungs and, and 3D imaging of the distribution of worm larvae may clarify preferential routes in this poorly-understood migration [42]. Likewise, flatworms of the genus Schistosoma migrate through skin and lungs, with chronic infection featuring egg-associated granulomas in the liver, intestine or bladder and other organs [43].…”
Section: Worms Exhibit "Head Down" Behaviormentioning
confidence: 99%
“…A. suum is often postulated as a model for research on human infection by Ascaris lumbricoides Linnaeus, 1758. Human ascariasis affects approximately 820 million people, most often the younger generations, especially in areas with poor access to water, sanitation and hygiene [ 2 , 3 , 4 , 5 ]. It is standard to use large-scale preventive chemotherapy to control for geohelminths due to the large epidemic threat [ 6 ].…”
Section: Introductionmentioning
confidence: 99%